β-Hydroxyisovaleryl-Shikonin Exerts an Antitumor Effect on Pancreatic Cancer Through the PI3K/AKT Signaling Pathway - Zeng, Yu; Zhang, Haifeng; Zhu, Minghui; Pu, Qingfan; Li, Jinhai; Hu, Xiao (Frontiers in Oncology, 2022)
Pancreatic cancer (PC) is marked with low survival rate and lack of recognized effective treatment strategy. We investigated the antitumor effect of β-hydroxyisovaleryl-shikonin (β-HIVS) on PC, and the associated working mechanism. Cell toxicity was determined using Cell Counting Kit-8 (CCK-8) assay. Acridine Orange/Ethidium Bromide (AO/EB) double-fluorescent staining assay accompanied with flow cytometry were utilized to estimate cell apoptosis. Cell cycle, reactive oxygen species (ROS) and mitochondrial membrane potential were all evaluated using flow cytometry. Transwell and wound healing assays were performed to evaluate cell migration and invasion. Protein expression were analyzed by Western blots. A xenograft mouse model was employed to determine the antitumor effect of β-HIVS in vivo. PC cell viability gradually decreased with increasing β-HIVS while apoptosis was enhanced together with cell cycle blockage in G0-G1 phase. β-HIVS induced mitochondrial dysfunction, ROS production and DNA damage, and inhibited the invasive and migratory ability of PC cells. We further confirmed the suppression of EMT and PI3K/AKT pathways as underlying mechanisms. The mouse model treated with the increasing dose of β-HIVS displayed decreased tumor growth rate, along with increased apoptosis. Thus, β-HIVS exerts anti-tumor effects on PC through inducing apoptosis, ROS production, decreasing mitochondrial membrane potential as well as suppressing signal pathways, such as PI3K/AKT. In summary, β-HIVS might be a promising strategy for PC treatment.